Application of the fuzzy analytic hierarchy process to the lead-free equipment selection decision. (3rd December 2010) - Tang, Yu-Cheng; Lin, Thomas W.
After 1 July 2006, a major challenge that the manufacturing industry has to confront now is the effect of the lead-free equipment system selection process on companies' capital expenditure decision. With capital investment, the criteria may be financial (e.g. expected cash flows) and non-financial (e.g. product quality). We use a systems approach with the fuzzy analytic hierarchy process (FAHP) method as the decision support system to help decision makers making better choices both in relation to tangible criteria and intangible criteria. Fuzzy set theory will be utilised to provide an effective way of dealing with the uncertainty of human subjective interpretation of tangible and intangible criteria.